Database Design, Application Development, and Administration - Mannino Michael V (McGraw Hill/Irwin, 2004)
Mannino’s Database Management provides the information you need to learn relational databases. The book teaches students how to apply relational databases in solving basic and advanced database problems and cases. The fundamental database technoloiges of each processing environment are presented; as well as relating these technologies to the advances of e-commerce and enterprise computing. This book provides the foundation for the advanced study of individual database management systems, electrnoic commerce applications, and enterprise computing.